An evidence review of data associated with non-domestic buildings - Vatougiou, Paraskevi; McCallum, Peter; Jenkins, David (Heriot-Watt University, 2022)
Scotland’s Heat in Buildings Strategy sets out a pathway to zero emissions buildings by 2045 and details actions that will accelerate the transformation of the nation’s building stock. The Strategy commits to the conversion of the equivalent of 50,000 non-domestic buildings to zero emissions heat by 2030. There are approximately 220,000 non-domestic buildings in Scotland and these buildings are hugely diverse. An understanding of the merits and limitations of existing building stock data is integral to developing policy that supports the Heat in Buildings Strategy commitment. This report, commissioned by the Scottish Government, reviews available data that describes the non-domestic stock in Scotland. Whilst the key focus is limited to this specific geographic and sectoral scope, the background review is informed by studies from the UK and elsewhere, and work in other sectors. The report also provides a link between available data sources and non-domestic building policy areas, providing a framework to encourage evidence-based policy-making.
Keywords: heat in buildings; non-domestic; building stock data; Scotland; Zero emissions heat